A comparison of two low-calorie sweeteners and sugar in dark chocolate on sensory attributes and emotional conceptualisations. (3rd April 2018) - Lagast, Sofie; De Steur, Hans; Schouteten, Joachim J.; Gellynck, Xavier
Abstract: Reducing sugar consumption is an important aspect in the prevention of and fight against obesity. A broader understanding of consumers' perceptions of low-calorie sweeteners is needed. This study examined two low-calorie sweeteners, tagatose and stevia, in comparison to sugar in dark chocolate. A total of 219 consumers participated in this study and rated overall liking and sensory attributes. Participants also listed their emotional conceptualisations upon consumption and were assessed on emotional eating behaviour and health and taste attitudes. The chocolate with tagatose was perceived as more similar to the chocolate with sugar than with stevia on overall liking, texture, bitterness, duration of aftertaste and intensity of aftertaste. Furthermore, chocolate with sugar and chocolate with tagatose both elicited positive emotional conceptualisations whereas chocolate with stevia elicited negative emotional conceptualisations. In conclusion, dark chocolate with tagatose did not significantly differ from sugar in overall liking, most sensory attributes and emotional conceptualisation.